Sistem Informasi Madrasah Diniyah Mesjid Al-Marhamah Berbasis Online - Deval Gusrion (Universitas Putra Indonesia YPTK Padang, 2019)
Madrasah Diniyah is a non-school religious educational institution that is expected to deliver Islamiceducation continuously beyond the teachings that already exist in regular school. As an educational institution, within it, there are several aspects such as grades and attendance that haven’t beenmonitored well, especially by parents, thus these parent are in ableto know the grades & attendance of their children in the given time.With an online-based application, it is possible forparents, teachers and MDA management to know the knowledge development of these students (santri) through aspects such as grades, attendance, Al-Qur’an recitation and etc. , so the students achievements can be monitored well by teacher and parents.